MAMMOGRAPHIC DENSITY AS A CRITERION OF THE EFFICIENCY OF TREATMENT OF BENIGN BREAST DISEASE AND REDUCING RISK OF BREAST CANCER - V. G. Bespalov; Yu. F. Negustorov (ABV-press, 2017)
High mammographic density (MD) is a risk factor of breast cancer. The article discusses the relationship between MD and risk of breast cancer and proliferative benign breast disease (BBD), the impact of BBD treatment on MD. The types of MD according to BI-RADS (Breast Imaging Reporting and Data System) are considered. High MD is an independent and strong risk factor for breast cancer, proliferative BBD and precancerous lesions in mammary tissue. Long-term pathogenetic treatment of BBD reduces MD. The drug progestogel, transdermal micronized progesterone, eliminates the imbalance of estrogens and progestins in the mammary tissue, which is the main pathogenic mechanism of the development of BBD. The clinical experience of the evaluation of the effect of progestogel on MD is presented. Progestogel® in monotherapy was prescribed to patients with BBD in the form of cutaneous applications once a day, daily 2.5 g per each mammary gland for 3 months. Patients underwent 3 courses of treatment for 3 months with a break between courses of 1 month. Before the treatment and 1 year after the treatment, mammography was performed. Progestogel reduced MD in patients with BBD.Mammography with an evaluation of MD is recommended as an objective criterion for evaluating the efficiency of treatment of BBD and chemopevention of breast cancer.